Effect of Grafting on Viral Resistance of Non-transgenic Plum Scion Combined With Transgenic PPV-Resistant Rootstock - Sidorova, Tatiana; Miroshnichenko, Dmitry; Kirov, Ilya; Pushin, Alexander; Dolgov, Sergey (Frontiers in Plant Science, 2021)
In stone fruit trees, resistance to Plum pox virus (PPV) can be achieved through the specific degradation of viral RNA by the mechanism of RNA interference (RNAi). Transgenic virus-resistant plants, however, raise serious biosafety concerns due to the insertion and expression of hairpin constructs that usually contain various selective foreign genes. Since a mature stone tree represents a combination of scion and rootstock, grafting commercial varieties onto transgenic virus-tolerant rootstocks is a possible approach to mitigate biosafety problems. The present study was aimed at answering the following question: To what extent are molecular RNAi silencing signals transmitted across graft junctions in transgrafted plum trees and how much does it affect PPV resistance in genetically modified (GM)/non-transgenic (NT) counterparts? Two combinations, NT:GM and GM:NT (scion:rootstock), were studied, with an emphasis on the first transgrafting scenario. Viral inoculation was carried out on either the scion or the rootstock. The interspecific rootstock ‘Elita’ ((Prunus pumila L.  P. salicina Lindl.)  (P. cerasifera Ehrh.)) was combined with cv. ‘Startovaya’ (Prunus domestica L.) as a scion. Transgenic plum lines of both cultivars were transformed with a PPV-CP-derived intron-separate hairpin-RNA construct and displayed substantial viral resistance. High-throughput sequence data of small RNA (sRNA) pools indicated that the accumulation of construct-specific small interfering RNA (siRNA) in transgenic plum rootstock reached over 2%. The elevated siRNA level enabled the resistance to PPV and blocked the movement of the virus through the GM tissues into the NT partner when the transgenic tissues were inoculated. At the same time, the mobile siRNA signal was not moved from the GM rootstock to the target NT tissue to a level sufficient to trigger silencing of PPV transcripts and provide reliable viral resistance. The lack of mobility of transgene-derived siRNA molecules was accompanied by the transfer of various endogenous rootstock-specific sRNAs into the NT scion, indicating the exceptional transitivity failure of the studied RNAi signal. The results presented here indicate that transgrafting in woody fruit trees remains an unpredictable practice and needs further in-depth examination to deliver molecular silencing signals.